2008
DOI: 10.1007/s10350-007-9149-4
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Durability of Super-Selective Embolization in the Treatment of Lower Gastrointestinal Bleeding

Abstract: This large series reaffirms the high success rate (97 percent) and relatively low acute ischemia risk (7 percent) of super-selective embolization for lower gastrointestinal bleeding. Furthermore, only 15 percent of patients ultimately required readmission for recurrent bleeding. It is our recommendation that super-selective embolization be used as the primary therapeutic modality in the treatment of angiogram positive lower gastrointestinal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 25 publications
1
39
0
2
Order By: Relevance
“…The short-term results in our study are very close to other experiences reported in the literature. For example, Lipof et al [13] reported immediate hemostasis in 97 % of the patients, with short-term rebleeding in 16 % of patients and acute ischemia in 7 % of patients. Table 3 resumes the short-term results reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The short-term results in our study are very close to other experiences reported in the literature. For example, Lipof et al [13] reported immediate hemostasis in 97 % of the patients, with short-term rebleeding in 16 % of patients and acute ischemia in 7 % of patients. Table 3 resumes the short-term results reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It also demonstrates the efficacy of this procedure as a definitive treatment for LGIB. In the literature, Lipof et al [13] reported 15 % of recurrences of hemorrhage (8 patients out of 71) with a mean follow-up of 32 months. Tan et al [25] reported 13 % of rebleeding at 30 days or more after the first episode (4 of 32 patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] However, innovations in coaxial technique have allowed for a superselective approach to bleeding vessels, resulting in continued high rates of haemostasis with reduced instances of ischaemia. Numerous studies in recent years have demonstrated this benefit, [11][12][13][14][15][16][17] contributing to the overall acceptance of embolization as a legitimate and even preferred treatment option in the management of acute massive colonic haemorrhage. Additionally, direct comparisons of embolotherapy with catheter-directed vasoconstrictive therapy (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prior published data on endovascular technique is limited by a majority of studies using a combination of different embolic agents to manage lower GI bleeding, consequently confounding the evaluation for efficacy of any one single agent. 4,[11][12][13][14][15][17][18][19]25,27,28 The present study sought to address this concern by examining both early and delayed rebleeding rates in patients managed specifically by superselective microcoil embolization, yielding rates of 11.5% and 15.3%, respectively. These findings take an initial step at showing the ability to achieve long-term haemostasis in most patients treated by endovascular coiling alone.…”
Section: Discussionmentioning
confidence: 99%